ITC Event Management System - Syed Mohd, Syed Muhamad Alif; Nur Liyana Sulaiman (Applied Information Technology And Computer Science, 2025)
The ITC Event Management System is a web-based platform developed for the ITC Club, a student organization in the Faculty of Science Computer and Information Technology at UTHM. Previously, the club faced problems with the manual event proposal submission process, which often led to communication breakdowns, scheduling conflicts, and considerable inefficiencies among its executive committees. The objective is to design an ITC Event Management System using object-oriented approach, develop a web-based approach and to test using user acceptance testing. The software process used was the Prototyping Model and the architecture pattern adopted was Model-View-Controller (MVC). During testing, overall test result of the test cases is 81.08% pass and only 18.92% fail. Alpha testing achieved a 100% pass rate and beta testing achieved 87.2%. This system streamlines event proposal submissions, facilitates event details sharing, and manages paperwork thus improve the event management process at the ITC Club.